A educação da infância pobre em Sergipe: a Cidade de Menores Getúlio Vargas (1942-1974) - Bispo, Alessandra Barbosa (2007)
To talk about the History of the Minors City Getúlio Vargas is an effort to comprehend the history of the poor childhood in Sergipe. The Minors City Getúlio Vargas was set in the county of Nossa Senhora do Socorro Sergipe (1942-1974). The temporal delimitation of the study considered 2 fundamental moments of the institution the year that was opened in 1942, until the year that was closed in 1974. when the minors were sent to another institution. The duty of Minors City was to assist and educate abandoned and delinquent minors that were from 7 to 18(seven to eighteen) years old, in a boarding-school regime. At this establishment, they had basic, professional and agricultural education. Its location showed an observable strategy at the same time painstaker and hygienist by being distant from the center of Aracaju. The assistance institution to the abandoned and delinquent minor in Sergipe was in the national project to the assistance to the minor and received influences of the hygienist address that saw in these children a threat to society, in agreement with the civilized project of the country and with the criminality theories defenders of the State intervention.